2015
DOI: 10.14238/pi55.1.2015.06
|View full text |Cite
|
Sign up to set email alerts
|

Association between passive smoking and Mycobacterium tuberculosis infection in children with household TB contact

Abstract: Background Tuberculosis (TB) and cigarette consumption are relatively high in Indonesia. Passive smoking may increase the risk of infection and disease in adults and children exposed to TB. An association between passive smoking and Mycobacterium tuberculosis infection in children has not been well documented. Objective To assess for an association between passive smoking and M. tuberculosis infection in children who had household contact with a TB patient. Methods This cross-sectional study was conducted in F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…tuberculosis infection. The progression of latent to active tuberculosis has been directly associated with impairment of the immune systems and defects in immune cell responses [ 41 , 42 ]. Therefore, early diagnoses with better diagnostic tools and treatment of known TB cases as well as reducing other contributing risk factors are important in the preventions and controlling of the transmission of TB infections.…”
Section: Discussionmentioning
confidence: 99%
“…tuberculosis infection. The progression of latent to active tuberculosis has been directly associated with impairment of the immune systems and defects in immune cell responses [ 41 , 42 ]. Therefore, early diagnoses with better diagnostic tools and treatment of known TB cases as well as reducing other contributing risk factors are important in the preventions and controlling of the transmission of TB infections.…”
Section: Discussionmentioning
confidence: 99%
“…The odds ratio for being asthmatic in ETS-exposed as compared to ETS-unexposed children was 1.78 (95% CI: 1.33-2.31) . 11 . Another study demonstrated exposure to ETS was a significant trigger for acute exacerbation of asthma.…”
mentioning
confidence: 99%